Genetically Engineered IL12/CSF1R‐Macrophage Membrane‐Liposome Hybrid Nanovesicles for NIR‐II Fluorescence Imaging‐Guided and Membrane‐Targeted Mild Photothermal‐Immunotherapy of Glioblastoma - Pengfei Chen; Yue Liu; Haiyan Huang; Menglong Li; Hui Xie; Shubham Roy; Jingsi Gu; Jian Jin; Kai Deng; Lixin Du; Bing Guo (Advanced Science)
Abstract It is a big challenge for precision therapy of glioblastoma, mainly due to the existence of blood–brain barrier (BBB), tumor immunosuppressive microenvironment (TIM), and lack of efficient treatment paradigms. Herein, a theranostic nanoplatform for the second near‐infrared window (NIR‐II) fluorescence imaging‐guided membrane‐targeted mild photothermal‐immunotherapy of glioblastoma using genetically engineered CSF1R/IL12‐macrophage membrane (MM)‐liposome hybrid nanovesicles, is reported. By mimicking lipophilic membrane probe (Dil) with octadecyl chains, a NIR‐II emissive photothermal dye (IRC18), which realizes labeling of nanovesicle lipid bilayers for biodistribution tracing, glioblastoma diagnosis, and molecular imaging of tumoral microenvironment, is synthesized. Importantly, MM and c‐RGD‐decorated liposome together offer BBB crossing, tumor targeting, and long‐term circulation; while, the genetically overexpressed CSF1R and IL12 on MM surface contribute to effective modulation of M2‐to‐M1 macrophage repolarization and local promotion of T cell cytotoxicity in glioblastoma microenvironment, respectively. Notably, through membrane fusion, IRC18 dyes translocate from nanovesicle lipid bilayers to glioblastoma membranes, which achieve membrane‐targeted mild photothermal therapy to ablate primary tumor and induce immunogenic cell death to promote antigen presentation. More importantly, the combined blockade of the CSF1‐CSF1R axis and IL‐12 enrichment not only reprograms the tumor microenvironment through macrophage M1 repolarization but also activates cytotoxic T cells, ultimately achieving complete glioblastoma eradication. This research provides an efficient theranostic paradigm for glioblastoma treatment.